1998
DOI: 10.1111/j.1349-7006.1998.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine‐stimulated Intracellular Ca2+ Release for Invasiveness of Rat Ascites Hepatoma Cells

Abstract: Our previous study showed that treatment of highly invasive rat ascites hepatoma (LC-AH) cells with α α α α-difluoromethylornithine (DFMO), an inhibitor of ornithine decarboxylase, decreased both their intracellular level of putrescine and their in vitro invasion of a monolayer of calf pulmonary arterial endothelial (CPAE) cells, and that both these decreases were completely reversed by exogenous putrescine, but not spermidine or spermine. Here we show that all adhering control (DFMOuntreated) cells migrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that exogenous putrescine induced transformation of rat ascites hepatoma cells from nonmigratory to migratory cells and that this change in their behavior was preceded by an increase in the level of their intracellular Ca 2ϩ [10]. The effect of the added putrescine was suppressed by ryanodine, a blocker of cyclic ADP-ribose-triggered Ca 2ϩ release from the ER.…”
Section: Activation Of Caspases In Mouse Myeloma Cells Accumulating Ementioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have demonstrated that exogenous putrescine induced transformation of rat ascites hepatoma cells from nonmigratory to migratory cells and that this change in their behavior was preceded by an increase in the level of their intracellular Ca 2ϩ [10]. The effect of the added putrescine was suppressed by ryanodine, a blocker of cyclic ADP-ribose-triggered Ca 2ϩ release from the ER.…”
Section: Activation Of Caspases In Mouse Myeloma Cells Accumulating Ementioning
confidence: 96%
“…Polyamines were demonstrated to block and modulate several types of ion channels. In rat ascites hepatoma cells, exogenous putrescine induces an increase in their intracellular Ca 2ϩ level [10]. In contrast, in CD4 but not in CD8 T-cells, putrescine inhibits concavalin-A-induced Ca 2ϩ influx [11], demonstrating that the effect of polyamine can be cell dependent.…”
Section: Introductionmentioning
confidence: 94%
“…Notably, these effects were suppressed by antisense oligonucleotides of ODC [32]. Also, treatment with DFMO inhibited the in vitro invasion of LC-AH rat ascites hepatoma cells [34], and that of GaMg, U-251 and U-87 human glioma cell lines [35].…”
mentioning
confidence: 99%